Solar cooling and heating : architectural, engineering, and legal aspects - Solar Cooling and Heating Forum (1976 : Miami Beach, Florida); Veziroglu, T. Nejat; University of Miami. Clean Energy Research Institute; United States. Energy Research and Development Administration (Washington : Hemisphere, 1978)
03